Trichoderma diversity from karst area in Yunnan, Shilin, and four new species - Dai, Xing-Wen; Zhang, Xian-Kun; Li, Xiao-Hui; Li, Qian-Qian; Zhang, Feng; Qiao, Min; Mo, Ming-He; Huang, Ying; Yu, Ze-Fen (Frontiers in Microbiology, 2025)
Trichoderma spp. are widely distributed across diverse environments and play a significant role in both ecosystem stability and economic applications. In this study, 57 Trichoderma strains were isolated from karst desert soil, of which 47 strains were identified as nine known species, while 10 strains were characterized as belonging to four novel species. Phylogenetic analyses, based on the combined sequences of the internal transcribed spacer (ITS), translation elongation factor 1-alpha (tef1-α), and RNA polymerase II second largest subunit (rpb2) genes, confirmed their distinct taxonomic positions. The results indicate that these four species are distributed across three known clades. Detailed morphological descriptions, cultural characteristics, and illustrations are provided for each new species, and comparisons are made with closely related taxa. The four new species are named Trichoderma calcicola, Trichoderma exigua, Trichoderma karsti, and Trichoderma xerophilum. This study documents the diversity of Trichoderma in rocky desertification ecosystems that remain agriculturally productive, suggesting their potential ecological adaptation to nutrient-poor, drought-prone, and calcium-rich soils, with implications for future biotechnological and biocontrol applications.